PUSAT INFORMASI PARIWISATA DAN KEBUDAYAAN SULAWESI DENGAN PENDEKATAN ARSITEKTUR MODERN - Fadillah, Andi Nur; Arfan, Taufik; Rahayu, Irma (Nature : National Academic Journal of Architecture, 2014)
Plaining and desaign aims to design a tourism information and culture center with Modern arhitecture approach, this designlimited on several issue there arethe architectural issue, particulary spatial, space recurements and appearance of the building, while the method used is the study of literature/ literary studies, surveys (from of field observation and data collection of building where has a similar function to to tourism information and cultur center), and analyzing the data obtained. The result of the design is the creative of tourism information and culture South Sulawesi center in Makassar with modern architecture apptoach with the ablility of the building to accommodate the times when the building is nuanced and modern look, with a modern from so that, this building more interesting to prospective visitors.